Cylinder accuracy analysis of tangential turning of disk-like workpieces with increased cutting speed - Sztankovics, István (Journal of Production Engineering, 2024)
Tangential turning, a precision high-speed finishing procedure, is crucial for achieving superior surface quality and dimensional accuracy in cylindrical workpieces. This advanced machining technique leverages tangentially applied cutting forces to minimize tool deflection and vibration, thereby enhancing the surface integrity of the final product. Despite its advantages, tangential turning poses challenges in maintaining cylindrical accuracy, necessitating a thorough investigation of cylindrical error. Cylindrical error, the deviation of the machined surface from a perfect cylinder, significantly impacts the functional performance of precision components. Factors such as tool wear, machine dynamics, and thermal effects can induce these errors, demanding comprehensive studies to optimize process parameters and tool paths. By thoroughly analyzing cylindrical error, manufacturers can refine tangential turning processes, ensuring high precision and consistency in high-speed finishing operations. This research underscores the importance of precision error analysis in advancing manufacturing capabilities and achieving stringent quality standards. Cylindrical accuracy is analyzed using the full factorial experimental design methodology to carry out practical cutting experiments, where the cutting speed, feed, and depth of cut were the altered variables. The cylindricity error, peak maximum departure, their ratio, and coaxiality are measured and analyzed. The main effect analysis and detailed study are elaborated using the determined equation. It is found that decreasing the studied parameters is advisable if increasing cylinder accuracy is needed.